sl(2)ˆ Decomposition of denominator formulae of some BKM Lie superalgebras - II - Suresh Govindarajan; Mohammad Shabbir (Nuclear Physics B, 2023)
The square-root of Siegel modular forms of CHL ZN orbifolds of type II compactifications are denominator formulae for some Borcherds-Kac-Moody Lie superalgebras for N=1,2,3,4. We study the decomposition of these Siegel modular forms in terms of characters of two sub-algebras: one is a sl(2)ˆ and the second is a Borcherds extension of the sl(2)ˆ. This is a continuation of our previous work where we studied the case of Siegel modular forms appearing in the context of Umbral moonshine. This situation is more intricate and provides us with a new example (for N=5) that did not appear in that case. We restrict our analysis to the first N terms in the expansion as a first attempt at deconstructing the Siegel modular forms and unravelling the structure of potentially new Lie algebras that occur for N=5,6.